Histologic Variants of FSGS: An Epidemiological and Pathological Perspective. (Pakistan Journal of Kidney Diseases, 2021)
Focal segmental glomerulosclerosis (FSGS) is a conglomerate of glomerular pathological lesions unified by the segmental distribution of proliferative, sclerosing or collapsing lesions in less than 50% of glomeruli (i.e., focal distribution) in the early stages of the process and can only be diagnosed on renal biopsy. Epidemiologically, FSGS has acquired the top position among the causes of nephrotic syndrome (NS) in adults in many parts of the world and has emerged as the main cause of chronic kidney disease (CKD) and end-stage renal disease (ESRD) worldwide. Numerous approaches have been used to classify this lesion, but all have merits and demerits and no one system is entirely satisfactory. One of the popular schemes for the classification is based on morphological features and distribution of the lesions in the glomeruli, the so-called Columbia classification of FSGS. In this review, we briefly summarize the relevant epidemiology and pathology of FSGS variants in the light of our own experience with the use of this classification.
Keywords: FSGS; Histological classification; end stage renal disease; nephrotic syndrome; segmental